Recombinant human erythropoietin protects long-term cultured ageing primary nerve cells by upregulating the PI3K/Akt pathway. Issue 4 (9th February 2022) - Wang, Huqing; Chen, Ming; Gao, Zhen; Gong, Yu; Yu, Xiaorui; Wu, Haiqin
Abstract : Objective: Previous studies have found that recombinant human erythropoietin (rhEPO) protects long-term cultured ageing primary nerve cells by enhancing the endogenous antioxidant capacity of cells; however, its signalling pathways are not clear. This study aimed to explore the relationship between the rhEPO and PI3K/Akt pathways in the protection of senescent nerve cells at the cellular level. Methods: Primary nerve cells were cultured for 22 days to mimic the natural ageing process of nerve cells. rhEPO and LY294002 were administered as an intervention on the 11th day of culture. Western blot, immunochemistry, 3-(4, 5-dimethyl-thiazol-2-yl)-2, 5-diphenyltetrazolium bromide, immunofluorescence double-labelling staining, Annexin V-FITC/PI double-labelling flow cytometry, and SA-β-gal staining experiments were used to observe the expression levels of erythropoietin receptor (EPOR) and phosphorylated Akt (p-Akt) protein and the related indices of nerve cell senescence. Results: Western blot experiments showed that in ageing long-term cultured primary neurons, the EPOR and p-Akt decreased and rhEPO upregulated the expression levels of EPOR and p-Akt protein. The rest showed that the PI3K/Akt pathway blockade reduced the antioxidation capacity, cell viability, cell morphology, and ratio of apoptotic cells and senescent cells of rhEPO on ageing long-term cultured primary nerve cells. Conclusions: This study explored the relationship between the rhEPO and PI3K/Akt pathways in the protection of ageing nerve cells at the cellular level and found that rhEPO protects long-term cultured ageing primary nerve cells by upregulating the PI3K/Akt pathway. These findings provide a theoretical basis and experimental evidence for the antiaeging mechanism of EPO in the nervous system.